I Did It Mathematics Book - 7 - Rupesh Pathak (Cambridge, United Kingdom Cambridge University Press, 2022)
The revised edition of 'I Did It' Mathematics is a carefully-graded, activity-based mathematics series. The aim of this series is to make the learning of mathematics a thoroughly enjoyable experience. The series conforms to the vision of the National Curriculum Framework. The revised edition of the series offers enhancements that facilitate the learning of mathematical concepts. It provides plenty of opportunities to explore concepts through individual and collaborative work. At the same time it paves the way for advanced learning through engaging methods of instruction. In this edition, the unique approach to concept-learning through diverse multi-sensorial activities is preserved. In addition, continuity in learning has been ensured through fortified lesson plans that include assessments at the beginning and end of the chapters. The series will also cater to Multiple Intelligences and hence will give students opportunity to learn in the manner that is best suited to them.
Keywords: PY - Mathematics -- PY - Mathematics